Copper‐Catalyzed S‐Arylation Starting from Arylboronic Acids and Tetraalkylthiuram Disulfide. Issue 6 (13th February 2018) - Xu, Wan; Gao, Fan; Dong, Zhi‐Bing
Abstract : A convenient and useful protocol for the synthesis of diverse S ‐aryl dithiocarbamates was studied. Starting from arylboronic acid and tetraalkylthiuram disulfide, copper‐catalyzed C–S coupling proceeds smoothly to give the desired S ‐aryl dithiocarbamates in good to excellent yields. The broad substrate scope, short reaction time, easy performance, cheap substrates, and nice yields make this approach attractive, showing its practical synthetic value for the preparation of some biologically or pharmaceutically active compounds. Abstract : In the presence of Cu2 O and pyridine, arylboronic acids couple with tetraalkylthiuram disulfides smoothly to furnish the desired phenyl dithiocarbamates in good to excellent yields. The broad substrate scope, short reaction time, commercially available cheap substrates, easy performance, and nice yields make this approach attractive.